2010
DOI: 10.1177/193229681000400320
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mixing Efficiency of Neutral Protamine Hagedorn Cartridges

Abstract: Abbreviations: (HPLC) AbstractReliable application of neutral protamine Hagedorn (NPH) insulin requires previous resuspension of the suspension by tipping over the cartridge 20 times. This procedure is considered annoying by patients. The goal of this investigation was to assess the efficiency of the mixing procedure when performed less frequently than recommended. Neutral protamine Hagedorn insulin cartridges from five different manufacturers (sanofi-aventis, Lilly, Berlin-Chemie, B. Braun, and Novo Nordis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The wide fluctuations in plasma glucose control reported in subjects with T1DM who do not adequately resuspend NPH insulin before injection (10) are likely explained by the PK/PD results of the current study. A large part of the reported variability of NPH insulin (5-7,10,18) is possibly explained by a lack of or insufficient resuspension before injection, as shown in the current study; thus, the variability of NPH insulin might be substantially decreased in the everyday life of patients with diabetes by simply adhering to the long-well-known recommendation of resuspending NPH insulin before injection, no matter the manufacturer (19). In fact, the major insulin companies all recommend injecting NPH insulin at room temperature after full resuspension obtained with at least 10-20 times of tipping the pen to allow full movement of the small glass ball present in the Novo Nordisk FlexPen and Lilly KwikPen or the three small metal balls of the Sanofi Lantus SoloSTAR pen.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The wide fluctuations in plasma glucose control reported in subjects with T1DM who do not adequately resuspend NPH insulin before injection (10) are likely explained by the PK/PD results of the current study. A large part of the reported variability of NPH insulin (5-7,10,18) is possibly explained by a lack of or insufficient resuspension before injection, as shown in the current study; thus, the variability of NPH insulin might be substantially decreased in the everyday life of patients with diabetes by simply adhering to the long-well-known recommendation of resuspending NPH insulin before injection, no matter the manufacturer (19). In fact, the major insulin companies all recommend injecting NPH insulin at room temperature after full resuspension obtained with at least 10-20 times of tipping the pen to allow full movement of the small glass ball present in the Novo Nordisk FlexPen and Lilly KwikPen or the three small metal balls of the Sanofi Lantus SoloSTAR pen.…”
Section: Discussionmentioning
confidence: 94%
“…However, the fact that differences are quite evident with so few subjects speaks in favor of the importance of the resuspension process as a main factor in determining PK/PD of injected NPH insulin. The study examined NPH insulin from only one manufacturer (Novo Nordisk), but it is assumed that NPH insulin from other manufacturers would result in similar characteristics (19) and action profiles at least in subjects without diabetes (24). In the present study, the effect of NPH insulin was examined for 24 h after administration of a 0.35 units/kg dose, mimicking the subjects' prior daily basal insulin need (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IDegAsp provides full 24-h coverage of basal insulin requirements as shown by a distinct peak action due to prandial IAsp and separate and stable basal action from IDeg (20). The low variability of the IDeg component reported at steady state over a 24 h period (12,21) could further contribute to the low rates of hypoglycemia observed with IDegAsp.…”
Section: Discussionmentioning
confidence: 99%
“…As a soluble coformulation, IDegAsp does not require resuspension, which eases administration (11) and, more importantly, eliminates the risk of incomplete mixing and therefore increased hypoglycemia (12). In solution, the individual components of IDegAsp exist separately as di-hexamers (IDeg) and hexamers (IAsp) (13).…”
mentioning
confidence: 99%
“…In this issue of Journal of Diabetes Science and Technology, Kaiser and colleagues 11 conducted an investigation to identify variations in the delivered dose of several different NPH insulin brands that use glass and metal bodies ("bullets") to facilitate mixing. Using a strategy where multiple pens from each of five different NPH insulin products (Insuman Basal, sanofi-aventis, three metal bullets; Humulin N, Lilly, one glass bullet; Berlinsulin H Basal, Berlin-Chemie, one glass bullet; Insulin B. Braun Basal, two glass bullets; and Protaphane Penfill, NovoNordisk, one glass bullet) were compared at multiple sampling points and over a range of mixing procedures (3, 6, 10, and 20 times), the authors identified deviations in the delivered dose of insulin at initial use and with repeated dosing.…”
Section: Brief Study Reviewmentioning
confidence: 99%